1988
DOI: 10.1530/acta.0.1170249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol on the progesterone receptor and on morphological ultrastructures in the fetal and newborn uterus and ovary of the rat

Abstract: The effect provoked by estradiol after administration to pregnant rats (1 mg per day) was studied in fetal and newborn uteri and ovary. Estrogen receptors are found in the fetuses of non-treated animals.Their number (in fmol/mg DNA,\ m=+-\ sd) in the fetal uterus (total sites, cytosol + nuclei) was at the age of 18 days: 63 \ m=+-\15; at 20 days 101 \ m=+-\13; and in the 24-h-old newborn; 415 \ m=+-\ 120. The respective values in the ovary were: 105 \ m=+-\ 25; 520 \m=+-\ 60 and 410 \m=+-\ 190. Estradiol stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…It has been shown that the intensities of CD15 immunoreactivity in the endometrial cells of normal untreated rats vary greatly during the estrous cycle (Staneva-Dobrowski and Mai 1993). In the present study we found changes in the expression levels of CD15 during the late prenatal and early postnatal period (in the genital tract) which could be clearly correlated with the temporal profiles of the concentration of either serum estrogen or estrogen receptors in the rat uterus (Clark and Gorski 1970;Medlock et al 1981;Nguyen et al 1988). Serum estrogen concentration is very high until the second postnatal day and declines until P8.…”
Section: Significance Of the Present Findingssupporting
confidence: 70%
“…It has been shown that the intensities of CD15 immunoreactivity in the endometrial cells of normal untreated rats vary greatly during the estrous cycle (Staneva-Dobrowski and Mai 1993). In the present study we found changes in the expression levels of CD15 during the late prenatal and early postnatal period (in the genital tract) which could be clearly correlated with the temporal profiles of the concentration of either serum estrogen or estrogen receptors in the rat uterus (Clark and Gorski 1970;Medlock et al 1981;Nguyen et al 1988). Serum estrogen concentration is very high until the second postnatal day and declines until P8.…”
Section: Significance Of the Present Findingssupporting
confidence: 70%
“…In rat uterus, ER is known to increase in number after birth and reach a maximum by 10 days of age (Clark and Gorski, 1970), while PR is not detectable in newborns (Nguyen et al, 1988) and the progesterone-binding sites are markedly lower in infants than in adults (Milgrom and Baulieu, 1970). These findings indicate that the ability of endometrial cells to synthesize receptor proteins may be involved in the uterine maturation.…”
Section: Discussionmentioning
confidence: 92%
“…In rats, moreover, a critical period of the uterine ability responding to progesterone has been found in a postnatal life (Ohta, 1981). The rat uterine progesterone receptor (PR) has been reported to be absent in newborns (Nguyen et al, 1988) and markedly lower in infants than in adults (Milgrom and Baulieu, 1970). It seems likely that development of PR, as well as ER, is involved in a requirement for a postnatal factor to induce uterine maturation.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that neonatal ovaries contain some substance that can bind progesterone (16). The progesterone receptor antagonist RU-486 was unable to completely inhibit progesterone actions, and the antagonist was found to have some agonist activity.…”
Section: Discussionmentioning
confidence: 99%